KAJIAN OPERASIONAL ANGKUTAN UMUM DI KABUPATEN BARITO TIMUR - Reilly Hard (Jurnal Teknologi Berkelanjutan, 2013)
Tamiang Layang Terminalis the placewhere the activities of transporting passengers in TamiangLayang, East Barito Regency, occur. Economic developmentandpopulationgrowth which are quite high inEast Barito Regency bring impact on increaseddemandfor the means of transportation. Nowadays, a problem in public transportation routes occurs. The problem is in some regions where the number of the public transport users is quite big, the public transport users have not been servedproperly; therefore,in-depth researchis neededtoovercome the problem. This research aims at evaluating the performance of public transportation in East Barito Regency and to determine out the number of ideal transport fleets, the fare and fleet scheduling. The current evaluation of the performance of public transport which is based on the standard of Directorate General of Transportation and World Bank, shows that the average performance of routes is still in conformance with the standard with the average waiting time of approximately 21 minutes, the average travel time of 69 minutes, the average speed of 24,88 km/h, the load factor of 43 percent, the average number of passengers of 23 people/vehicles/day, the utility of vehicles of 93 km/vehicles/day, and the availability level of vehicles of 81 percent. Based on the scheduling, it is obtained that the number of fleet on route 1 is 10/7 trip; on route 2, route 4, route 6 are 8/9 trip; and on route 3 androute5are12/6 trip. Based on the result of the analysis, it is obtained that the lowest fare is Rp 1.000 on route 1 and the highest fare is Rp 9.000 on route 3 and route 5, while the current lowest fare is Rp 5.000 on route 1 and route 6, and the current highest fare is Rp 10.000 on route 4 and route 5.